2019
DOI: 10.1111/bjd.18387
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and long‐term sequelae in survivors of epidermal necrolysis: an observational study of 57 patients

Abstract: Summary Background Few studies have investigated the global burden of sequelae and health‐related quality of life (HRQoL) for survivors of epidermal necrolysis (EN). Objectives To investigate the long‐term HRQoL for survivors of EN using validated instruments. Methods We conducted a single‐centre study that enrolled patients who were admitted for EN between 2010 and 2017. HRQoL was assessed via phone interview using the Short Form (SF)‐36 questionnaire, Hospital Anxiety and Depression (HAD) scale, Impact of Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
0
26
0
3
Order By: Relevance
“…Comparing the DTS and the PCR, the overall concordance rate was 92% (72/78; j-coefficient: 0.84), which is considered as an almost perfect agreement between the two diagnosis methods PCR. Two previous studies 5,6 demonstrated the superiority of DTS as compared to DME (Table 1). Our data confirm the high performance rates of DTS as compared to DME and PCR.…”
Section: Diagnosis Of Toenail Onychomycosis By An Immunochromatographic Dermatophytes Test Stripmentioning
confidence: 87%
See 1 more Smart Citation
“…Comparing the DTS and the PCR, the overall concordance rate was 92% (72/78; j-coefficient: 0.84), which is considered as an almost perfect agreement between the two diagnosis methods PCR. Two previous studies 5,6 demonstrated the superiority of DTS as compared to DME (Table 1). Our data confirm the high performance rates of DTS as compared to DME and PCR.…”
Section: Diagnosis Of Toenail Onychomycosis By An Immunochromatographic Dermatophytes Test Stripmentioning
confidence: 87%
“…1). 5 We conducted a prospective observational study to assess DTS (Diafactory Tinea unguium, JNC corporation, Japan and Biosynex, Fumouze Diagnostics, Illkirch-Graffenstaden, France) on toenails with suspicion of onychomycosis and compared the results to DME and PCR. Seventy-eight patients were included.…”
Section: Diagnosis Of Toenail Onychomycosis By An Immunochromatographic Dermatophytes Test Stripmentioning
confidence: 99%
“…The overall mortality of the acute phase is around 15% [ 6 ]. Most survivors have more or less severe sequelae, usually cutaneous, ocular, and psychological, with long-term impact on the quality of life [ 7 ]. Twenty to 79% of patients present with potentially vision-threatening chronic ocular manifestations [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the extent of epidermal detachment, epidermal necrolysis is classified as Stevens–Johnson syndrome (SJS; <10% of the skin affected), Lyell syndrome, also known as toxic epidermal necrolysis (TEN; ≥30% of the skin affected) or overlap syndrome (10–29% of the skin affected) 1 . There is a variety of possible sequelae in the long term which significantly impair quality of life 5 . They mainly include ophthalmological sequelae, 6 fibrotic, pigmentary or dysaesthetic cutaneous and mucosal scars, pulmonary lesions, 7 psychological disorders 8 and chronic pain.…”
Section: Introductionmentioning
confidence: 99%